2017
DOI: 10.5194/nhess-17-243-2017
|View full text |Cite
|
Sign up to set email alerts
|

A method to estimate freezing rain climatology from ERA-Interim reanalysis over Europe

Abstract: Abstract. A method for estimating the occurrence of freezing rain (FZRA) in gridded atmospheric data sets was evaluated, calibrated against SYNOP weather station observations, and applied to the ERA-Interim reanalysis for climatological studies of the phenomenon. The algorithm, originally developed at the Finnish Meteorological Institute for detecting the precipitation type in numerical weather prediction, uses vertical profiles of relative humidity and temperature as input. Reanalysis data in 6 h time resolut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…To characterize these variables, the 1981-2011 average was determined for each station and mapped across the country. Assessment of the trend can be challenging for time series with low occurrences and repetitive (tied) values (Frei andSchär, 2001 andKeim andCruise, 1998), such as the annual number of days with certain precipitation types. A χ 2 test was applied to the data to determine whether the data followed a normal or Poisson distribution.…”
Section: Methodsmentioning
confidence: 99%
“…To characterize these variables, the 1981-2011 average was determined for each station and mapped across the country. Assessment of the trend can be challenging for time series with low occurrences and repetitive (tied) values (Frei andSchär, 2001 andKeim andCruise, 1998), such as the annual number of days with certain precipitation types. A χ 2 test was applied to the data to determine whether the data followed a normal or Poisson distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Freezing rain represents a threat for the power transmission lines as it could lead them to fail. Several examples are listed in the literature and they include blackouts affecting up to 80% of the population in some countries, and more than 200 km of power lines and major cities such as Moscow [59]. Again, climate change may have an impact on this meteorological phenomenon: it has been found that for eastern Canada the intra-annual distribution of freezing rain events will change as they will be more frequent from December-February and less frequent in other months by the end of this century [60].…”
Section: Cold Wavesmentioning
confidence: 99%
“…Freezing rain-"rain that falls in liquid form but freezes upon impact to form a coating of glaze upon the ground and on exposed objects" [1]-is a meteorological phenomena more frequently observed in Europe during the winter months (i.e., December-February) [2,3]. The extensive ice accumulation on the ground associated with freezing rain can lead to a significant impact on human activities, surface and air transportation, infrastructure and electrical power transmission [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several impactful freezing rain events occurred in Europe. For example, a freezing precipitation event that occurred between 25-26 December 2010 in Moscow, Russian Federation affected the public (i.e., power lines were destroyed) and air transport (i.e., flights were cancelled at the Domodedovo Airport) [3]. In 2014, the freezing rain events that occurred between 31 January-4 February over the Balkan Peninsula resulted in 10 cm accumulation of ice in Slovenia and damages estimated at EUR 400 million [29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation